2010
DOI: 10.1002/esp.2071
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian sand strip mobility and protodune development on a drying beach: examining surface moisture and surface roughness patterns measured by terrestrial laser scanning

Abstract: Ephemeral aeolian sand strips are commonplace on beaches. Their formation during high energy sand transport events often precedes the development of protodunes and their dynamics present interesting feedback mechanisms with surface moisture patterns. However, due to their temporary nature, little is known of their formation, mobility or the specifics of their interaction with beach surface characteristics. Similarly surface moisture has an important influence on sediment availability and transport in aeolian b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 54 publications
3
101
0
Order By: Relevance
“…As the beach dries out, the distensions are dispersed by the wind. The same forms was observed by Nield (2011) and Rotnicka (2013b) on the beach of the Łeba Barrier, southern Baltic Sea coast, Poland.…”
Section: Resultssupporting
confidence: 85%
“…As the beach dries out, the distensions are dispersed by the wind. The same forms was observed by Nield (2011) and Rotnicka (2013b) on the beach of the Łeba Barrier, southern Baltic Sea coast, Poland.…”
Section: Resultssupporting
confidence: 85%
“…In the context of vegetated ground surfaces, the intensity may also be influenced by edge effects. Nield et al (2011) found that the moisture content of soils affected the intensity of the survey data acquired in a beach environment. Thus it is difficult to identify a general algorithm that can identify different types of materials based solely on the intensity recorded by the TLS.…”
Section: Intensity Methodsmentioning
confidence: 99%
“…Apart from discrete topography measurements, almost all current TLS instruments simultaneously measure the power of the backscattered laser signal of each point and record it as an intensity value [3]. The intensity recorded by current laser scanners, either in the form of the echo amplitude or full-waveform of the backscattered laser signal [4], can be utilized as complementary information along with the point cloud in a wide range of applications, especially in visualization, segmentation [5], classification [6][7][8][9][10], and multi-temporal analysis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The intensity value is regarded as a significant source of spectral information associated with the surface properties, e.g., reflectance [1,[15][16][17][18], roughness [15,19], moisture [11,13,14,20,21], brightness [22][23][24][25] and grain size [26,27], of the scanned object. However, the original intensity data 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation